2021
DOI: 10.3390/ijerph18189805
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health as a Predictor of Physical Frailty among Rural Community-Dwelling Elderly in an Agricultural County of Taiwan: A Cross-Sectional Study

Abstract: We conducted a cross-sectional study to clarify the relationship between oral health and physical frailty (PF). A sample of 903 community-dwelling individuals aged ≥ 65 years were enrolled from random communities in Chiayi County. The self-perceived oral health (SPOH) and oral health assessment tool (OHAT), which consists of eight items, was used for the evaluation of their oral health status. PF was assessed based on the Study of Osteoporotic Fracture index. Overall, 14.6% of the participants had PF. In an ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Self-reported health status levels of fair and poor were also found to be indispensable predictors for PF in this study. Self-perceived oral health with restricted food types and dental status was significantly associated with PF [ 35 ]. Elderly people with cognitive decline may require guidance for self-reported oral frailty problems, which could improve their oral health.…”
Section: Discussionmentioning
confidence: 99%
“…Self-reported health status levels of fair and poor were also found to be indispensable predictors for PF in this study. Self-perceived oral health with restricted food types and dental status was significantly associated with PF [ 35 ]. Elderly people with cognitive decline may require guidance for self-reported oral frailty problems, which could improve their oral health.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found that there was a significant association between tooth loss and a greater likelihood of frailty among older nursing home residents, which was in line with previous studies. In a study covering 903 community-dwelling older adults, the number of teeth was associated with frailty, with an OR = 0.98 (95% CI: 0.96-0.99) [17]. In addition, a cohort study with 3 years of follow-up among home-dwelling individuals aged 70 or older indicated that one additional tooth could lower the risk of frailty by 5.0% [14].…”
Section: Discussionmentioning
confidence: 99%
“…In 2013, Andrade and colleagues explored the association between oral health and frailty among older community-dwelling adults, and the results showed that participants with 20 or more teeth had a lower likelihood of being frail than those with edentulism [12]. In recent decades, a growing body of studies have indicated that tooth loss leads to a high risk of frailty in both cross-sectional and prospective cohort studies [13][14][15][16][17]. In addition, studies have also found that poor oral behavior can lead to a high risk of frailty among community-dwelling older adults.…”
Section: Introductionmentioning
confidence: 99%
“…To date, multiple studies have explored the relationship between the number of teeth and frailty. However, the relationship remains uncertain, and whether the risk of frailty increases as the number of teeth decreases is a matter of debate 9,10 . Some studies have linked decreasing in the number of teeth to the risk of frailty in old adults, one of the biggest medical challenges facing older adults today 1,[11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…The pathways between number of teeth and frailty may be nutrition, in ammation and so on 1 .The decrease in the number of teeth can reduce the chewing function of older adults, thus affecting their food choices and causing them to avoid eating hard foods that are di cult to chew 9 . As a result, with lower intake of fruits, vegetables, and proteins, the risk of malnutrition increases and therefore, frailty comes 10 .…”
Section: Introductionmentioning
confidence: 99%